2020
DOI: 10.3390/cancers12102849
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Endoscopic Submucosal Dissection for Superficial Esophageal Squamous Cell Carcinoma

Abstract: In this review, we summarize up-to-date reports with 5-year survival after endoscopic submucosal dissection (ESD) for superficial esophageal squamous cell carcinoma. In ESD for the depth of the epithelium (m1) or lamina propria (m2), the 5-year cause-specific survival and 5-year overall survival rates were reported to be 98–100%, and 85–95%, respectively. In cases with submucosal invasion or vascular involvement, additional prophylactic treatment such as chemoradiotherapy or surgery was recommended, and the 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 45 publications
3
42
2
Order By: Relevance
“…Moreover, through the combined therapy of ER and RFA, the background esophageal mucosa was significantly improved postoperatively (70.2%), especially for patients with preoperative background esophageal mucosa assessed as Grade D (80.2%). Besides, compared with that of previous studies (6,7,15,32), the additional RFA for multiple LVLs on the basis of ER of early ESCNs did not increase the incidence of postoperative complications. Thus, this combination treatments for patients with early ESCNs and synchronous multiple LVLs not only can give full play to the advantages of complete resection of the primary lesions and pathological evaluation postoperatively but also can leverage the advantages of RFA in the treatment of dense, scattered, and irregular multiple LVLs.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Moreover, through the combined therapy of ER and RFA, the background esophageal mucosa was significantly improved postoperatively (70.2%), especially for patients with preoperative background esophageal mucosa assessed as Grade D (80.2%). Besides, compared with that of previous studies (6,7,15,32), the additional RFA for multiple LVLs on the basis of ER of early ESCNs did not increase the incidence of postoperative complications. Thus, this combination treatments for patients with early ESCNs and synchronous multiple LVLs not only can give full play to the advantages of complete resection of the primary lesions and pathological evaluation postoperatively but also can leverage the advantages of RFA in the treatment of dense, scattered, and irregular multiple LVLs.…”
Section: Discussionmentioning
confidence: 46%
“…Keisuke et al (5) found that most of the LVLs with size less than 5 mm were diagnosed as non-neoplastic lesion (42.1%) or low-grade intraepithelial neoplasia (LGIN) (54.0%) according to pathological results of the biopsy or resected specimens. Patients with dysplasia and superficial ESCC (intramucosal or submucosal carcinoma) exhibit an overall 5year survival rate of >90% (6).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 5-year survival rates are low (5–15%) but significantly improve when diagnosis is made at early stages [ 5 ]. Notably, a 95% 5-year survival rate has been reported given early diagnosis [ 6 ]. Despite several ongoing efforts for early detection of ESCC in endemic areas [ 7 ], a minimally invasive and feasible approach has yet to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The 5-year cause-specific survival and 5-year overall survival rates were reported to be 98-100% and 85-95% in endoscopic submucosal dissection (ESD) of the depth of the epithelium (EP) or lamina propria mucosae (LPM), respectively. 14 White-light endoscopy (WLE) is the standard modality for detecting esophageal neoplastic lesions. However, the endoscopic features of early esophageal neoplastic lesions under WLE are subtle and isochromatic.…”
Section: Introductionmentioning
confidence: 99%